VE-PTP controls a fluid shear stress set point that governs cell morphological responses through Tie-2 - Shirakura, Keisuke; Ghanbarpour Houshangi, Mana; Peters, Kevin G.; Vestweber, Dietmar (Frontiers in Cell and Developmental Biology, 2025)
Blood flow differs between arteries and veins, hence endothelial cells in these vessels are exposed to different magnitudes of shear stress. Deviation from physiological blood flow triggers vascular remodeling, with increased or decreased flow leading to outward or inward remodeling, to adjust lumen diameter and thereby re-establish physiological shear stress. Based on this, it is assumed that endothelial cells in different vessels differ in their sensitivity to different shear stress levels. Expression levels of VEGFR3 were previously demonstrated to determine the threshold or set point for endothelial cell type specific shear stress sensitivity. Here we show, that the receptor type tyrosine phosphatase VE-PTP and the tyrosine kinase receptor Tie-2 represent another, new signaling system, that determines sensitivity and cellular responsiveness to different shear stress magnitudes or flow set points. We found that increased shear stress levels cause increased levels of VE-PTP endocytosis, which trigger, a similarly graded increase of Tie-2 activity, stimulation of FOXO1 nuclear exclusion and activation of autophagy. The VE-PTP/Tie-2 signaling mechanism controls cell alignment and elongation dependent on the magnitude of shear stress. In addition, VE-PTP/Tie-2 controls shear stress-induced cellular morphological changes independent of VEGFR2. Thus, VE-PTP/Tie-2 is a novel signaling mechanism which determines shear stress sensitivity and morphological responses of endothelial cells.